Corruption as an empty signifier : politics and political order in Africa - Koechlin, Lucy (African-Europe Group for Interdisciplinary Studies (Series), 2013)
Corruption as an Empty Signifier critically explores the ways in which corruption in Africa has been equated with African politics and political order, and offers a novel approach to understanding corruption as a potentially emancipatory discourse of political transformation.